2018
DOI: 10.1177/1120672118757657
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes of pediatric traumatic cataracts

Abstract: Phacoaspiration with posterior chamber intraocular lens implantation along with primary posterior capsulotomy and anterior vitrectomy and timely introduction of amblyopia therapy helped in gaining good visual outcome in pediatric traumatic cataract patients irrespective of the age of presentation and the type of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 12 publications
(18 reference statements)
11
23
1
Order By: Relevance
“…Some studies that have investigated the effects of trauma type on the nal visual acuity have revealed that blunt traumas have a better prognosis than penetrating traumas [10,14,[17][18][19]. A statistically signi cant relationship was not found between the type of trauma and the nal visual acuity in the current study, similar to two previous studies [4,16]. With both trauma types, the presence of ocular pathologies besides cataracts, as well as other factors that could in uence the nal vision, may explain the different results reported in various studies.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Some studies that have investigated the effects of trauma type on the nal visual acuity have revealed that blunt traumas have a better prognosis than penetrating traumas [10,14,[17][18][19]. A statistically signi cant relationship was not found between the type of trauma and the nal visual acuity in the current study, similar to two previous studies [4,16]. With both trauma types, the presence of ocular pathologies besides cataracts, as well as other factors that could in uence the nal vision, may explain the different results reported in various studies.…”
Section: Discussionsupporting
confidence: 85%
“…We observed PCO in all of the 13 cases over 9 years of age that did not undergo PC+AV, as in a previous study [15]. According to statistical analyses, the nal CDVA was signi cantly better in patients that had undergone PC+AV compared to those that did not undergo this procedure [5,16,19]. Therefore, the use of posterior capsulotomy and anterior vitrectomy for traumatic pediatric cataract surgery will help to avoid a high postoperative PCO rate (100% in our cases) and the complications that could develop due to YAG capsulotomy or surgical interventions to treat PCO in older children as well.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations